ANALYSIS THE EFFECT OF WORK REQUEST TECHNOLOGY ON CLOUD-BASED FACILITIES MANAGEMENT (CFM) APPLICATIONS ON EMPLOYEE PERFORMANCE AT TRILLIUM OFFICE & RESIDENCE: ANALISIS PENGARUH TEKNOLOGI WORK REQUEST PADA APLIKASI CLOUD-BASED FACILITIES MANAGEMENT (CFM) TERHADAP KINERJA KARYAWAN DI TRILLIUM OFFICE & RESIDENCE - Wira Utama, Alvani Fahrizal; Wibawa, Rindu Puspita (Universitas Negeri Surabaya, 2024)
A Work Request is a document (digital or paper) in which there is a request for assistance from internal or external business partners for a task that must be completed. With a work request, all data information related to the needs and planning of a job can be fulfilled. The application that has this technology in it is CFM (Cloud-based Facilities Management). This research uses the Task Technology Fit model combined with the perceived usefulness variable from the Technology Accepiance Model (TAM).This research aims to determine the suitability of work request technology tasks for Trillium Office & Residence employees who use the CFM application. Data collection for the research was carried out by distributing an online questionnaire to 33 respondents. These respondents are Trillium Office & Residence employees who use the CFM application. In this study, data analysis used PLS-SEM. The results of the research are that there are 7 hypotheses which have been proven to have a positive and significant influence on all respondents who use the CFM application.